Implementasi senam kaki mandiri dalam managemen nyeri diabetes (Gerakan Lansia Tangguh) - Yuli Susanti; Arista Adityasari Putri (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Diabetes Mellitus (DM) is a chronic disease whose prevalence continues to increase globally, including in Indonesia. Impaired glucose regulation due to abnormalities in insulin secretion and function leads to increased blood glucose levels, potentially leading to various metabolic complications. At the national and regional levels, the number of DM sufferers continues to increase annually, including in Central Java Province, which shows a significant upward trend. One of the most common complications experienced by DM sufferers, especially in the elderly, is diabetic neuropathy. The prevalence of diabetic neuropathy in type 2 DM reaches more than 50%, making it a major cause of decreased quality of life in the elderly and a risk factor for diabetic ulcers. Karang Anyar Regency also reports a high number of type 2 DM sufferers accessing health services, thus increasing the risk of neuropathy. Management of diabetic neuropathy relies not only on pharmacological therapy but also non-pharmacological interventions. One intervention that has been proven effective and easy for the elderly to perform is diabetic foot exercises. This community service activity was conducted in Karang Anyar District by the Ahad Pagi community. The goal was to provide foot health education and facilitate the practice of diabetic foot exercises to reduce neuropathic pain, improve blood circulation, and support the independence of older adults in maintaining lower extremity health. Purpose: To provide education and support for diabetes management in older adults through independent foot exercises to address joint pain. Method: This community service was conducted through an initial survey by the team to all organizing committees of the Sunday Morning Study with PCM Karang Anyar Regency. The target of this activity was the management of diabetes in the elderly by implementing foot exercises. The activity with the theme